DYNAMICS OF CONFLICT AND COLLABORATION BETWEEN LOCAL AND CENTRAL GOVERNMENT - Azharisman Rozie; Selvi Meilinda; Dwi Agus Sumarno; Hendayana Hendayana; Riko Wijaya (Journal of Research in Social Science and Humanities, 2024)
This study conducted a review of the literature to analyze the dynamics of conflict and collaboration between local and central government in Indonesia. The aim of this research is to identify patterns and trends in these dynamics, as well as the underlying factors. The research presents findings from various articles and academic works that highlight changes in the relationship over time, challenges faced, as well as strategies used to improve intergovernmental cooperation. The research findings show that conflicts between local and central governments are often related to resource struggles, differences in interests, and lack of coordination. For example, conflicts related to the management of natural resources, such as forests and mining, often occur because local and central governments have different interests in their utilization. In addition, differences in regulations and policies between the two levels of government can also trigger conflict. On the other hand, collaboration between local and central governments is driven by factors such as common goals, effective communication, and strong leadership. This collaboration can be realized through various forms, such as cooperation in the preparation and implementation of development programs, exchange of information and data, and coordination in solving common problems. The results of this study provide valuable insights for practitioners at different levels of government to understand and effectively manage intergovernmental conflict and collaboration. Practitioners at the local and central government levels need to improve communication and coordination to minimize conflict and maximize collaboration. In addition, clear and consistent regulations and policies are needed at both levels of government to support effective collaboration. This research makes a new contribution to the understanding of the dynamics of the relationship between local and central government in Indonesia by identifying key factors that drive conflict and collaboration. It also demonstrates the important role of communication, coordination and leadership in building harmonious and productive intergovernmental relations.